Dynamic Analysis of the Motion of a Vibrating Mechanical System (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This article focuses on vibrating the working bodies of soil tillage machines, and methods of increasing energy and resource efficiency and reducing traction resistance by vibrating their working bodies are researched.